The significance of colors according to Ibn al-Rumi - Shatti, Salma; Rad , Hassan (Al-Adab Journal, 2025)
Poetry is representation and depiction, before it is ornate language and adorned speech. Just as we marvel at the artist’s precision when he highlights the light and shadows, the colors and shapes of an image, so too we marvel at the poet’s alert senses when he depicts for us in his poetry and verses what the artist draws with his brush and colors. And when the poet shows us the beauty of the eyes, the magic of the eyelids, the redness of the cheeks, and the prominence of the breasts, through representation and depiction, not with a brush and colors. Both artists represent reality, except that the artist shapes it in form and colors, and the poet conveys it through feeling and emotion. It may be rare for the artist to combine the imagination of the poet and the poet’s precision. For both of these aspects, each has risen to the throne of art. So which of the two men was Ibn al-Rumi? Ibn al-Rumi was an artist, a skilled painter, with a keen sense, deeply affected by nature, as if his nerves were electrical wires and his eyes were the lens of a camera, imprinting various scenes and images. It’s as if his ear - a microphone - was entrusted with capturing the subtlest and most sublime sounds. Ibn al-Rumi was also a naturally gifted poet, with a vast imagination, fertile feelings, and a passionate passion. While Abu al-Ala’ deserves to be called the poet of philosophers and the philosopher of poets, Ibn al-Rumi deserves to be called the poet of painters and the painter of poets. His poetry displays the precision of the painter and the multiplicity of his colors, the splendor of the poet’s imagination, and the sublimity of his emotions. When he describes a singing girl, you are captivated by his poetry’s passionate emotion and fertile imagination, followed by precise depiction and mastery of natural colors.